2000
DOI: 10.1016/s0022-5223(00)70231-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in whole blood lactate levels during cardiopulmonary bypass for surgery for congenital cardiac disease: An early indicator of morbidity and mortality

Abstract: Hyperlactatemia occurs during cardiopulmonary bypass in patients undergoing operations for congenital cardiac disease and may be an early indicator for postoperative morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
113
4
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(130 citation statements)
references
References 20 publications
8
113
4
5
Order By: Relevance
“…Munoz et al demonstrated that an increase in lactate level during CPB is an early indicator of a poor outcome (Munoz et al 2000). We showed that lactate measurements were more predictive of MAEs in the early post-CPB period.…”
Section: Fig 3 Periopetraive Hemodynamic Variables In the Mae Groupsupporting
confidence: 51%
See 1 more Smart Citation
“…Munoz et al demonstrated that an increase in lactate level during CPB is an early indicator of a poor outcome (Munoz et al 2000). We showed that lactate measurements were more predictive of MAEs in the early post-CPB period.…”
Section: Fig 3 Periopetraive Hemodynamic Variables In the Mae Groupsupporting
confidence: 51%
“…Postoperative hyperlactatemia as a result of tissue hypoperfusion is associated with high morbidity and mortality, and the serum or plasma lactate level in the intensive care unit (ICU) has prognostic value after pediatric cardiac surgery (Cheifetz et al 1997;Charpie et al 2000, Cheung et al 2005, Basaran et al 2006). In addition, hyperlactatemia during cardiopulmonary bypass (CPB) is an early predictor of morbidity and mortality in pediatric patients (Munoz et al 2000, Ranucci et al 2006. However, some confounding factors, such as the inhibition of pyruvate dehydrogenase, enhanced glycolysis, and an exogenous lactate load from red blood cells, can decrease the predictive power of lactate levels (McAuliffe et al 1986, Gilfix et al 1993.…”
mentioning
confidence: 99%
“…[14][15][16] Shemie [14] reported that major complications occurred in 32 of 109 patients, and that lactate levels were higher in patients with complications (8.6±6.1 mmol/L vs 3.2±1.9 mmol/L). Duke et al [15] reported 12 serious complications in 90 pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac output within the first 24 hours, oxygen delivery, mixed venous oxygen saturation, heart rate, and the difference of peripheral-central temperature did not have an effect on major adverse events. Munoz et al [16] investigated the arterial lactate levels before, during (cooling and warming-up), and after CPB, and upon ICU admission. Serious complications were defined as transfer to the intensive care unit with open sternum, development of renal failure, cardiac arrest, and requirement of resuscitation, requirement for ECMO, and death.…”
Section: Discussionmentioning
confidence: 99%
“…Не вызывает сомне ний, что тканевая гипоксия, в частности проявляющая ся гиперлактатемией, достоверно повышает риск осложнений после операций с ИК [10][11][12][13]. Вместе с тем, детальные исследования центральной гемодина мики (ЦГД) и ТК при разном темпе послеоперацион ной активизации до настоящего времени отсутствуют.…”
Section: центральная гемодинамика и транспорт кислорода при разном теunclassified